Edukasi Olahraga Pickleball Sebagai Inovasi Pembelajaran Pjok Bagi Guru Di Kecamatan Tallo Kota Makassar - Muh. Syachrul Syamsuddin; Ians Aprilo; Hasbi Asyhari; Muhammad Qasash Hasyim; Muhamamd Ivan Miftahul Aziz (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Pejuang Republik Indonesia, 2026)
This community service activity aims to provide education on pickleball as an innovative approach to Physical Education, Sports, and Health (PJOK) for teachers in Tallo District, Makassar City. Pickleball is a relatively new sport in Indonesia and is characterized by simple, engaging gameplay that is easy to implement in a school setting. However, many PJOK teachers are still unfamiliar with the rules, basic techniques, and teaching models for this sport. Therefore, this activity was conducted as an effort to broaden teachers’ knowledge and enhance their competencies in delivering more varied and enjoyable P.E., Sports, and Health lessons for students. The activity’s implementation methods included material presentations, training on basic pickleball techniques, game demonstrations, and hands-on practice involving all participants on the court. The activity was attended by PE teachers in Tallo Subdistrict using a participatory approach, ensuring participants not only received theoretical knowledge but also gained direct practical experience. Evaluation was conducted through observation and discussion regarding participants’ understanding and skills throughout the activity. The results of the activity showed that the teachers responded positively to the education provided. Participants were able to understand the basics of pickleball, ranging from game rules, serving techniques, hitting techniques, to the application of simple learning models in schools. This activity increased teachers’ enthusiasm for developing more creative, active, and adaptive Physical Education and Health (PJOK) learning innovations in response to the evolution of modern sports. With this initiative, pickleball is expected to become an engaging and easily implementable alternative for PJOK instruction within school settings, thereby benefiting students.